Different antibody responses between liver and kidney transplant recipients elicited by third doses of COVID-19 mRNA vaccines - So Yun Lim; Young-In Yoon; Ji Yeun Kim; Eunyoung Tak; Hyunwook Kwon; Sung Shin; Young Hoon Kim; Gi-Won Song; Sung-Han Kim; Sung-Gyu Lee (Korean Journal of Transplantation, 2023)
Background : Solid organ transplant recipients exhibit decreased antibody responses, mainly due to their weakened immune systems. However, data are limited on antibody responses after the primary series of coronavirus disease 2019 (COVID-19) vaccines among recipients of various solid organ transplant types. Thus, we compared the antibody responses after three COVID-19 vaccine doses between liver transplant (LT) and kidney transplant (KT) recipients. Methods : We prospectively enrolled solid organ transplant recipients who received three COVID-19 vaccine doses from June 2021 to February 2022 and measured S1-specific immunoglobulin G antibodies using an enzyme-linked immunosorbent assay. Results : Seventy-six LT and 17 KT recipients were included in the final analysis. KT recipients showed consistently lower antibody responses even after the third vaccine dose (86.2% vs. 52.9%, P=0.008) and lower antibody titers (median, 423.0 IU/mL [interquartile range, 99.6–2,057 IU/mL] vs. 19.7 IU/mL [interquartile range, 6.9–339.4 IU/mL]; P=0.006) than were observed in LT recipients. Mycophenolic acid was a significant risk factor for a seropositive antibody response after the third vaccine dose in the multivariable analysis (odds ratio, 0.06; 95% confidence interval, 0.00–0.39; P=0.02). Conclusions: We found a weaker antibody response despite the completion of the primary series of COVID-19 vaccines in KT recipients than in LT recipients. Mycophenolic acid use in KT recipients might be the main contributor to this observation.